Pulp capping: calcium silicate-based cements. Report of a clinical case - Yfuma Pedroza, Joshua Anggelo (2020)
Calcium silicate-based cements are bioactive materials, which have the capacity to release a greater number of calcium and hydroxyl ions, providing some advantages like an increased antimicrobial and remineralise activity, increasing the pulp treatments longevity. Theracal LC is a calcium silicate-based cement that has as an advantage its easy application, comparing to others bioactive cements. In this case report, Theralcal LC was used as a cavity liner. At clinical examination teeth 36 and 35 exhibited diagnosis of Dental caries; 36 with a cavitated lesion and 35 with a lesion adjacent to a previous restoration; and pulp diagnosis, Sound Pulp, for both tooth pieces. Direct restorations were made with composite resin in tooth pieces 36 and 35, considering the following steps: selective etching, self-etch adhesive system, calcium silicate-based cement and Bulk-ﬁll resin composite.